Development and demonstration of concentric-type HTS power cable for distribution grid in Shenzhen urban - Tang, Shouquan; Li, Minhong; Xie, Hong; Wang, Zhenzi; Yu, Peng; Li, Zhonghang; Wang, Zhe; Chen, Tengbiao; Wang, Bangzhu (Frontiers in Energy Efficiency, 2023)
High-temperature superconducting (HTS) cable can transmit massive power with little dissipation in a limited corridor, which is an attractive solution for future power transmission. Shenzhen Power Supply energized a 400 m/10 kV/2.5 kA concentric HTS cable system on 28 September 2021 to power Ping’an Financial Centre, a Shenzhen’s landmark building, which was the debut of concentric HTS cable made of YBCO in the urban area of a megacity. For more than one year, the HTS cable system has been operating well and will continue to operate for a long time. This paper systematically reviews the system specification, cable and its accessories design, cryogenic cooling system design, type and exploratory test, demonstration project construction, pre-commissioning test, and operation details of the Shenzhen cable system. Based on our R&D practice, we identify that cost, long-term reliability, and operational simplicity are the main hinders factors that need to be addressed to advance the large-scale application and we propose a set of solution ideas meanwhile.